Picrosirius-polarization staining method as an efficient histopathological tool for collagenolysis detectin in vesical prolapse lesions - Borges, Luciano Figueiredo; Gutierrez, Paulo Sampaio; Cosiski Marana, Heitor Ricardo; Taboga, Sebastiao Roberto (Elsevier B.V., 2007)
The Picrosirius-polarization method has been indicated as a selective histochemical stain for collagen detection in tissue sections. This method can also be of value for studying collagen degradation given that, under polarized light, collagen displays birefringence due to its molecular order. The aim of this study is to highlight this staining method as an additional instrument for a rapid and excellent confirmatory diagnosis of the presence of collagenolysis in connective tissue in the vaginal wall with vesical prolapse lesion, in tissue sections. Dramatic changes in collagen morphology were found in vaginal mucosa in vesical prolapse disorder: they were weakly stained by Sirius red and under polarized light appeared as thin, pale (weakly birefringent), greenish, and with fibers more scattered, while the histoarchitecture of the organ showed a disrupted appearance. Thus, in the present study, we showed in vaginal mucosa in the vesicle prolapse that corroded collagenous framework appears as fragmentary and irregularly separated collagenous structures, that are weakly birefringent, corresponding to a molecular disorganization of these fibers caused by collagenolysis. (C) 2006 Elsevier Ltd. All rights reserved.
Keywords: collagen; extracellular matrix; vesical prolapse; sirius red; collagenolysis